RADEC Learning Model (Read-Answer-Discuss-Explain And Create): The Importance of Building Critical Thinking Skills In Indonesian Context - Pratama, Yoga Adi; Sopandi, Wahyu; Hidayah, Yayuk (Universitas Malikussaleh, 2019)
The purpose of writing this article was to describe RADEC learning model in building critical thinking skills. This study was conducted because of the need for a learning model that fits the Indonesian context to build critical thinking skills that can be used at elementary school level. This study used the literature review. This study produced one solution to be able to build critical thinking skills using RADEC learning model (read-answer-discuss-explain and create). The approach in learning done by the teacher plays a role in improving critical thinking skills. The teacher needs to use a learning model that can stimulate students' critical thinking skills.